2016
DOI: 10.18632/oncotarget.11555
|View full text |Cite
|
Sign up to set email alerts
|

Promising pharmacological profile of a Kunitz-type inhibitor in murine renal cell carcinoma model

Abstract: Renal cell carcinoma (RCC), also called kidney cancer or renal adenocarcinoma, is highly resistant to current treatments. It has been previously reported that a Kunitz-type inhibitor domain-containing protein, isolated from the salivary glands of the Amblyomma cajennense tick, triggers apoptosis in murine renal adenocarcinoma cells (Renca) by inhibiting the proteasome and endoplasmic reticulum stress. Of note, Amblyomin-X is the corresponding recombinant protein identified in the cDNA library from A. cajennens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 32 publications
2
28
0
1
Order By: Relevance
“…Our results validated previous uses of Amblyomin-X against several tumor cell lines including skin melanoma [15][16][17][18]42 like ER-stress, Mitochondria-stress, and Apoptosis. It is important to note that the transcriptome results presented herein are the mean cell expression values in the tumor's core, a complex system composed of many distinct normal cells surrounding tumor cells.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results validated previous uses of Amblyomin-X against several tumor cell lines including skin melanoma [15][16][17][18]42 like ER-stress, Mitochondria-stress, and Apoptosis. It is important to note that the transcriptome results presented herein are the mean cell expression values in the tumor's core, a complex system composed of many distinct normal cells surrounding tumor cells.…”
Section: Discussionsupporting
confidence: 87%
“…This molecule has the ability to inhibit Factor Xa in the blood coagulation cascade and triggers apoptosis by activating its intrinsic pathway in tumor cells [14][15][16] . In previous studies, Amblyomin-X showed more avidity in the recognition of tumor cells, and rapid excretion in healthy murines 17 . We have already shown that Amblyomin-X causes cell death via induction of both endoplasmic reticulum (ER) stress and proteasome inhibition (PI) in renal adenocarcinoma (murine RENCA), in melanoma (murine B16F10 and human SK-MEL-28) 18 , as well as in pancreatic (human Mia-Paca-2) tumor cell lines 17,19,20 .…”
mentioning
confidence: 79%
“…The current study describes cellular effects induced by Kunitz-type inhibitor associated with distinct cell motility and proteolysis pericellular biological processes in tumor and endothelial cells. We have demonstrated before that Amblyomin-X has antitumor, antithrombotic and antimetastatic activity [25][26][27][28]. Interestingly, no cytotoxic effect was reported in non-tumor cells, such as fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…A recombinant form of this protein was shown to have strong pro-apoptotic activity in various murine and human tumor cells via endoplasmic reticulum stress (ER stress), proteasome inhibition, blockage of autophagy, cell cycle arrest, and aggregosome formation [ 22 24 ]. In vivo , we have shown that this inhibitor induces tumor regression and reduction of metastasis[ 25 ]. Furthermore, Amblyomin-X has no toxicity in normal cells and presents low toxicity in healthy animals [ 22 , 24 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prolongation of PT and aPTT is reversible [154]. Interestingly, several studies pointed out Amblyomin-X as an anti-cancer molecule in vitro and in vivo [154][155][156][157][158][159][160][161].…”
Section: Factor Xa Inhibitorsmentioning
confidence: 99%